ChemInform Abstract: Design, Synthesis and Antiproliferative Activity of Functionalized Flavone‐triazole‐tetrahydropyran Conjugates Against Human Cancer Cell Lines. Issue 51 (23rd December 2014) - Ahmed, Naseem; Konduru, Naveen Kumar; Ahmad, Sarfaraz; Owais, Mohammad
Abstract The title compounds were synthesized and tested against three human cancer cell lines (MDA‐MB 231, KCL22, and HeLa).